2009
DOI: 10.1159/000218162
|View full text |Cite
|
Sign up to set email alerts
|

Mortality after Nasogastric Tube Feeding Initiation in Long-Term Care Elderly with Oropharyngeal Dysphagia – The Contribution of Refeeding Syndrome

Abstract: Background: The refeeding syndrome (RS) is an underappreciated but clinically important entity characterized by acute electrolyte abnormalities, mainly hypophosphatemia, fluid retention and dysfunction of various organs and systems, which can result in significant morbidity and occasionally death. Objective: To examine the incidence of death cases and death causes following nasogastric tube (NGT) feeding initiation in frail elderly with particular reference to RS. Methods: Forty patients with feeding problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 45 publications
(27 reference statements)
1
20
0
5
Order By: Relevance
“…Hoffmann et al (4) showed a 30% mortality rate in hospitalized patients with severe hypophosphatemia. There was no increased mortality rate in the first 7 days of ICU stay in a study performed by Zeki et al (17), and, similarly, Lubart et al (30) did not find an increased mortality rate for 7 days and 1 month in 40 elderly patients with RH. In a study performed in 55 septic patients, severe hypophosphatemia increased mortality rates by 8-fold (2).…”
Section: Discussionmentioning
confidence: 69%
“…Hoffmann et al (4) showed a 30% mortality rate in hospitalized patients with severe hypophosphatemia. There was no increased mortality rate in the first 7 days of ICU stay in a study performed by Zeki et al (17), and, similarly, Lubart et al (30) did not find an increased mortality rate for 7 days and 1 month in 40 elderly patients with RH. In a study performed in 55 septic patients, severe hypophosphatemia increased mortality rates by 8-fold (2).…”
Section: Discussionmentioning
confidence: 69%
“…Lubart y cols. siguieron a 44 pacientes mayores que precisaban cuidados a largo plazo, a los que se les instauró NE por sonda nasogástrica por disfagia orofaríngea; al final de la primera semana de realimentación el 25% de los pacientes había presentado un fosfato sérico inferior a 1,6 mg/dl (11).…”
Section: Discussionunclassified
“…El 78,9% de los casos de hipofosfatemia se presentaron en los primeros cuatro días de SNE, lo que coincide con lo publicado en otros trabajos (11,13).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In a prospective study of mortality following NG tube feeding initiation in frail elderly, 65% died within 6 months of the tube insertion. Significant electrolytic disturbances were seen following NG feeding from baseline (p < 0.005) (76).…”
Section: Non-oral Non-surgical Tube Feedingmentioning
confidence: 94%